Peran Digital Marketing di Bidang Kewirausahaan dengan Metode Systematic Literature Review - Edo Rinaldi Rais; Jhon Veri (CV. ITTC INDONESIA, 2024)
This research focuses on the role of digital marketing in the field of entrepreneurship using a systematic literature review method. With advances in information technology, digital marketing plays a very important role in the field of entrepreneurship. This allows business actors to increase operational efficiency, expand market share, and can trigger new innovations in business. This research aims to systematically examine the role of digital marketing in the field of entrepreneurship, both the benefits and the platforms used. The method used to analyze 100 scientific articles is a systematic literature review, then extracted using covidence to produce PRISMA. The results of this research show that digital marketing has a big influence on the sustainability and improvement of businesses in the field of entrepreneurship. The platforms that can be used for digital marketing in the entrepreneurial sector include Instagram, Facebook, Youtube, Tiktok, E-Commerce, and Websites.